Trajectory analysis of a spacecraft making a three-dimensional powered swing-by maneuver - Ferreira, A. F.S. [UNESP]; Moraes, R. V. [UNESP]; Prado, A. F.B.A.; Winter, O. C. [UNESP] (My University, 2018)
The present paper studies the problem of orbital maneuvers performed combining the passage of a spacecraft by a celestial body with an impulse applied to the spacecraft during the close approach. The motion of the spacecraft is assumed to be in the three-dimensional space, thus allowing plane change. This type of maneuver can also send the spacecraft to a point far from the orbit or to end in capture or collision of the spacecraft by the celestial body. The effects of the variations in the orbital plane, energy and the angular momentum of the spacecraft are presented.